(untitled) (Journal of Humanitarian and Applied Sciences, 2023)
Abstract: This study aimed to evaluate the financial performance of the Libyan commercial banks after the conversion to Islamic banking, and North Africa Bank was chosen as a sample of study. Dupont model used to evaluate the financial performance of the bank under study based on a number of indicators, which are: Rate of return on equity (ROE), Rate of return on assets (ROA), Equity multiplier (EM), Profit margin (PM), and Asset benefit (AU). The evaluation done on the period before the conversion to Islamic banking for the years (2010, 2011, 2012), and the period after conversion to Islamic banking for the years (2015, 2016, 2017) In order to identify the impact of this transformation on the performance of the bank. The study reached a basic conclusion, which is the acceptance of the main hypothesis of the research that there are differences in the financial performance of the bank between the period before and after the transformation according to the evaluation results using the five indicators of the study model, and that all indicators were in favor of the period after the transformation except for the asset utility index (AU) whose evaluation was in favor of the pre-transformation period.